Retracted: Demethylation of miR‐195 suppresses prostate cancer cell proliferation, migration and invasion - Xiaokun Ma; Liyuan Zou; Zhanhong Chen; Xing Li; Li Wei; Xiangyuan Wu (FEBS Open Bio, 2020)
Prostate cancer (PCa) is the most prevalent cancer among men and the second leading cause of tumor‐associated deaths worldwide, with increasing incidence rates over the last 10 years. Recently, miR‐195 was reported to be hypermethylated at its promoter CpG island and down‐regulated in hepatocellular carcinoma. However, the function of miR‐195 and the underlying mechanisms in PCa remain unknown. Here, we report that a significant down‐regulation of microRNA‐195 (miR‐195) in PCa tissues and cell lines was associated with promoter methylation status. Overexpression of miR‐195 significantly suppressed cell proliferation, migration, invasion and epithelial–mesenchymal transition (increased E‐cadherin and decreased N‐cadherin) in PCa cells. We further demonstrated that transfection with a miR‐195 inhibitor reversed the inhibitory effect of the DNA methyltransferase inhibitor 5‐azacytidine on the proliferation, migration and invasion ability of PCa cells. In summary, our findings suggest that miR‐195 may function as a crucial tumor suppressor in PCa.